2021
DOI: 10.1038/s41598-021-86987-5
|View full text |Cite
|
Sign up to set email alerts
|

Geographically varying relationships of COVID-19 mortality with different factors in India

Abstract: COVID-19 is a global crisis where India is going to be one of the most heavily affected countries. The variability in the distribution of COVID-19-related health outcomes might be related to many underlying variables, including demographic, socioeconomic, or environmental pollution related factors. The global and local models can be utilized to explore such relations. In this study, ordinary least square (global) and geographically weighted regression (local) methods are employed to explore the geographical re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 21 publications
1
29
0
2
Order By: Relevance
“…Traditional OLS regression methods and spatial regression models have been used to understand the contribution of socioeconomic, demographic and environmental determinants to explain spatial variability of COVID-19 incidences and mortality in the epidemic ( Mansour et al, 2021 ; Maiti et al, 2021 ; Mena et al, 2021 ; Middya and Roy 2021 ; Mollalo et al, 2020 ; Zhang and Schwartz, 2020 ; Snyder and Parks, 2020 ). However, in the majority of these studies, only one regression-based method was employed.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional OLS regression methods and spatial regression models have been used to understand the contribution of socioeconomic, demographic and environmental determinants to explain spatial variability of COVID-19 incidences and mortality in the epidemic ( Mansour et al, 2021 ; Maiti et al, 2021 ; Mena et al, 2021 ; Middya and Roy 2021 ; Mollalo et al, 2020 ; Zhang and Schwartz, 2020 ; Snyder and Parks, 2020 ). However, in the majority of these studies, only one regression-based method was employed.…”
Section: Introductionmentioning
confidence: 99%
“…metropolitan, highly urbanised built environment, hyper-dense globalised population) such as London and Wuhan. However, this study also explores a different climatic facet given Singapore’s tropical climate, compared to those cities with temperate climates 28 , 47 .…”
Section: Discussionmentioning
confidence: 99%
“…In that direction, in relation to environmental and epidemiological characters, the study primarily focused on revealing spatial patterns, relations, geographical spread, dependency and intensity of COVID-19 in the respective sub-zones of Singapore using geospatial modelling and analysis techniques. Specifically, the Geographical Weighted Regression (GWR), which has been reported to be efficient in identifying the spatial variations 26 28 , was employed in this study. The spatial relationships among the sub-zones assessed in this study are (i) between environmental parameters and COVID-19 cases, (ii) between the level of urbanisation and population density and the COVID-19 cases, and (iii) among the three different type of epidemiological cases (linked, unlinked and imported cases).…”
Section: Introductionmentioning
confidence: 99%
“…Cumulative count data has been applied in studies of COVID-19, especially at a small-scale level such as neighborhood or county-level [ 57 ] and grid [ 58 ]. The study of [ 59 ] predicted cumulative confirmed and cured cases of COVID-19 at a province-level, while [ 60 ] considered the number of deaths. Furthermore, the use of count data as a dependent variable instead of some sort of rates at the neighborhood-level is advocated by [ 61 ], and it is widely applied in the context of studies of crime [ 62 ].…”
Section: Methodsmentioning
confidence: 99%